Drivers’ overtaking of bicycles with oncoming traffic: decision making process and safety margins towards cyclists - Moretto, Claudia (My University, 2017)
The use of bicycles is getting popular to go to work and school due to all the environmental issues, such as climate change. Furthermore, using a bicycle brings several advantages from a health as well as from an environmental point of view. However, the increasing usage of the bicycles has brought to an increase of situations when a motorist may need to overtake a slower bicycle. Consequently the likelihood to lead to severe injuries is increased. Several studies were carried out to investigate how drivers overtake cyclists, but more research is needed to assess the comfort zone boundaries during the overtaking maneuver of a cyclist in order to support the design of autonomous vehicles and countermeasures to road crashes. In fact, autonomous vehicles have to take into account every aspect that can occur during the driving, including safely overtaking a cyclist. A driving simulator study was conducted at the University of Tsukuba in Japan. The participants were requested to overtake the simulated bicycle with the presence of oncoming traffic in the opposite lane. Seven overtaking maneuvers were taken into account to simulate different values of time to collision (TTC) between the participant’s vehicle and the oncoming traffic. The results show that TTC significantly influences the overtaking strategy and the comfort zone boundaries chosen by the drivers during the overtaking maneuver. Besides, by comparing the current analyses with a previous study focusing on overtaking maneuvers without oncoming traffic, it was found that the participants reduced their safety margins to the bicycle due to the presence of oncoming traffic in the opposite lane. Further research is suggested to understand the factors affecting the decision making process during the overtaking maneuver. Furthermore, additional research should be conducted to evaluate how the lateral distance between the passing vehicle and the oncoming vehicle influences the choice of the comfort zone boundaries chosen by the driver towards the cyclist.
Keywords: Transport; Produktionsteknik, arbetsvetenskap och ergonomi; Transport; Production Engineering, Human Work Science and Ergonomics